The Implementation of quality management strategies: An empirical study of Guinness Nigeria - ADELANWA, Temitayo (2014)
The importance of quality to firms has progressively pervaded today’s markets as customer requirements and expectations have become more rigorous and challenging. According to Deming (1982), the only definition of quality that matters is that of the customer; therefore, a simple definition for quality is ‘products meeting or exceeding the expectations of customers’. There are various advantages of the implementation of Quality Management strategies in a company, some of which include: Strengthened competitive position, higher productivity, elimination of defects and waste, which leads to increase in profitability. This project will look into the Quality Management strategies being adopted by Guinness Nigeria in its operations by analyzing the initiatives adopted by the company and taking an in-depth look at the difficulty/ease they face in the implementation of quality strategies. In carrying out this extensive research on Guinness Nigeria, my aim is to analyze how well Quality Management techniques have been implemented and the challenges that have been faced during this implementation. The end of this research will achieve the following aims and objectives: • How has TQM been implemented in Guinness Nigeria? • Identify challenges that have been faced by organization. • Make recommendations for the improvement of quality management strategies. In finding out this information a detailed research that involves questionnaires and interviews will be carried out. The questionnaire aims to find out the opinions of employees in the organization; the interview also aims to find out the strategies that are being used by the organization. The information was analyzed by using the framework for the implementation TQM that is designed in this research. The analysis showed that TQM in Guinness Nigeria is very much being implemented, but it still needs to be developed. Some of the elements are present but need to be developed further, while some of the elements are non-existent. For Guinness Nigeria to successfully implement TQM, it will need to focus on the core elements of TQM and develop the supporting elements.